1995
DOI: 10.2136/sssaj1995.03615995005900010010x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Parameters of Pore Surface Area as Influenced by Simulated Soil Degradation

Abstract: Fractal parameters of soils become increasingly important in understanding and quantifying transport and adsorption phenomena in soils. It is not known yet how soil degradation affects fractal characteristics of soil pores. We estimated pore surface area fractal parameters from Hg porosimetry data on samples of a Udic Argiboroll, a Typic Haploboroll, and a Ustolic Orthid before and after simulated soil degradation. Three or four distinct intervals with different fractal dimensions were found in the range of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…As a rule, the fractal behavior of natural objects occurs in a limited range of scales, called upper and lower cutoffs [10]. A measure of the complexity of fractal structures is a fractal dimension, D, that is higher for more complex ones.…”
Section: Surface Fractal Dimensionmentioning
confidence: 99%
“…As a rule, the fractal behavior of natural objects occurs in a limited range of scales, called upper and lower cutoffs [10]. A measure of the complexity of fractal structures is a fractal dimension, D, that is higher for more complex ones.…”
Section: Surface Fractal Dimensionmentioning
confidence: 99%
“…The fractal dimension of mesopore surface, D mes , was calculated from the linear parts of log-log plots of the first derivative of pore volume as a function of radius vs. radius using the following dependence (Pachepsky et al, 1995):…”
Section: Calculations Of Pore Parametersmentioning
confidence: 99%
“…Later these authors suggested that a fractal Brownian motion can be a model for the soil water movement (Guerrini and Swartzendruber, 1994). Pachepsky et al (1995) conjectured that the fractal structure of soil pore space might cause an anomalous diffusion in soils.…”
Section: Introductionmentioning
confidence: 99%